KINETIKA ENZIM PEKTIN METIL ESTERASE (PME) ENDOGENOUS DARI PULP BIJI KAKAO - Ganda Putra, G.P. (Agrotekno, 2012)
This research was conducted to determine theenzymatic kinetics (Km and Vmax) of isolate of endogenouspectin methylesterase enzyme (PMEs) from cocoa pulp. Thisresearch was carried out by assaying the enzyme activity invarious pectin concentration used as substrate which its valuewas between 0.25 and 2.00% at 0.25% interval. The resultsshowed that the enzymatic kinetics of endogenous PMEsisolate from cocoa pulp in term of Km and Vmax were 15.75 ?gNaOH/minute/ml and 0.21%.
Keywords: enzymatic kinetics, PMEs, cocoa pulp